Students’ Perception of Google Classroom Implementation as Online Learning Media - Ketut Bayu Catur Paramahita; Ni Made Ratminingsih; Gede Mahendrayana (Journal of Educational Study, 2021)
The aim of this study was to discover high school students’ general perception about the implementation of Google Classroom as an online learning media, and the factors that influenced the development of the perception. This research used Mixed-method research design as described by Creswell (2014). Subject of this study was the student population of SMAS Lab Undiksha Singaraja. The instruments used for this research were Questionnaire and Interview Guide. The instruments were tested by using Gregory Formula Method and Cronbach-Alpha method. The data that have been obtained was analyzed using quantitative and qualitative method. The result of the research showed that the students of SMAS Lab Undiksha Singaraja held a positive view on the benefits of Google Classroom and its implementation as online learning media. Factors that have influenced this perception are Google Classroom’s ubiquity, students’ familiarity with Google Classroom, Google Classroom’s ease of use and stability in comparison to other similar applications.